(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study investigates the effects of Task-Based Language Teaching (TBLT) on pragmatic competence in multilingual EFL classrooms in Uzbekistan. Employing a mixed-methods quasi-experimental design, 60 intermediate-level learners were divided into an experimental group receiving TBLT instruction with translanguaging elements and a control group following traditional grammar-focused methods over 12 weeks. Pragmatic competence was assessed via Discourse Completion Tasks (DCT) and awareness questionnaires, supplemented by observations and interviews. Results revealed significant improvements in the experimental group, with large effect sizes in DCT scores (Cohen’s d = 1.92) and pragmatic awareness (d = 2.1), alongside qualitative themes highlighting pragmatic-related episodes and cultural negotiations. Findings underscore TBLT’s efficacy in fostering sociopragmatic and pragmalinguistic skills in diverse settings, advocating for its integration in multilingual education to enhance intercultural communication.